2016
DOI: 10.1016/j.jocn.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Meningioma after radiotherapy for malignancy

Abstract: Complications of radiation exposure have gained importance with increasing cancer survivorship. Secondary malignancies have been associated with cranial radiation exposure. We present our experience with intracranial radiation-induced meningioma (RIM) and discuss the implications of its presentation and natural history for patient management. Patients diagnosed with meningioma who had received radiation therapy between 1960 and 2014 were identified. Records were retrospectively reviewed for details of radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Six 6 events (50%) were likely related to RT. Caution must be heeded when administrating radiotherapy to brain tumors, as adverse events secondary to radiotherapy, not limited to but including cognitive impairment [26], pituitary dysfunction [27] and secondary brain tumors [28] are well known. The majority of Table 3 Emergent signs and symptoms # (using CTCAE version 3.0).…”
Section: Discussionmentioning
confidence: 99%
“…Six 6 events (50%) were likely related to RT. Caution must be heeded when administrating radiotherapy to brain tumors, as adverse events secondary to radiotherapy, not limited to but including cognitive impairment [26], pituitary dysfunction [27] and secondary brain tumors [28] are well known. The majority of Table 3 Emergent signs and symptoms # (using CTCAE version 3.0).…”
Section: Discussionmentioning
confidence: 99%
“…Radiation-associated meningiomas tend to occur at a younger age and are more often multiple when contrasted with sporadic meningiomas (Figure 13). 173,174 Radiation-associated gliomas are usually a high-grade astrocytoma occurring in the radiation field with imaging features indistinguishable from a primary glioma. 171 …”
Section: Imaging Of Treatment Responsementioning
confidence: 99%
“…They account for about 1-3% of pediatric CNS tumors (Dolecek et al 2012;Kaderali et al 2009). Meningiomas may occur as treatment related secondary cancers in pediatric patients within the radiation field; however they can be a long-term complication of cancer therapy, which may not present before adulthood (Morgenstern et al 2016). The majority of meningiomas are sporadic and may be asymptomatic (Kuratsu et al 2000), as 1-2% are first identified on autopsy (Nakasu et al 1987).…”
Section: Meningiomamentioning
confidence: 99%